2022
DOI: 10.3390/molecules27092902
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels: Properties and Applications in Biomedicine

Abstract: Hydrogels are crosslinked polymer chains with three-dimensional (3D) network structures, which can absorb relatively large amounts of fluid. Because of the high water content, soft structure, and porosity of hydrogels, they closely resemble living tissues. Research in recent years shows that hydrogels have been applied in various fields, such as agriculture, biomaterials, the food industry, drug delivery, tissue engineering, and regenerative medicine. Along with the underlying technology improvements of hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(175 citation statements)
references
References 237 publications
(324 reference statements)
2
110
0
Order By: Relevance
“…It has been observed that the transition process from CI to CII is accompanied by modifications of the intensities corresponding to different crystallographic planes. The diffraction peaks characteristic of CI are presented in Figure 4a and appear at Bragg angles (2θ) of 14.6°, 16.2°, and 22.5°, which are typical for the crystallographic planes, (110), (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), and (200), respectively. In the case of the CII, three characteristic cellulose lattice planes were identified in the XRD diffraction pattern (Figure 4b), and these appear at 12.1° assigned to the (110) plane, at 20.1° for the (1-10) plane, and at 21.8° for (200) plane, respectively.…”
Section: Crystallinity In Cellulose Allomorphs and Cellulose-based Hy...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the transition process from CI to CII is accompanied by modifications of the intensities corresponding to different crystallographic planes. The diffraction peaks characteristic of CI are presented in Figure 4a and appear at Bragg angles (2θ) of 14.6°, 16.2°, and 22.5°, which are typical for the crystallographic planes, (110), (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), and (200), respectively. In the case of the CII, three characteristic cellulose lattice planes were identified in the XRD diffraction pattern (Figure 4b), and these appear at 12.1° assigned to the (110) plane, at 20.1° for the (1-10) plane, and at 21.8° for (200) plane, respectively.…”
Section: Crystallinity In Cellulose Allomorphs and Cellulose-based Hy...mentioning
confidence: 99%
“…Since their development in the late 1960s, hydrogels have distinguished themselves by a network-like three-dimensional (3D) structure, as well as by their unique properties, which gives them competitive advantages compared to the other materials, making them a promising material-platform for various applications [ 1 , 2 , 3 ]. The undeniable versatility of hydrogels in terms of their synthesis, composition, and physical and chemical properties has led to a considerable attention from both research and industry and has created wide applicative potential, from the agricultural and industrial to the biomedical field.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen is one of the major structural elements of extracellular matrix (ECM) in bones, connective, and nerve tissues which are responsible for elastic strength, regulating cell adhesion, chemotaxis, migration, and tissue development. This polymer is the most abundant fibrous protein in the human body [ 90 , 91 ]. Collagen has challenges such as inconsistency, and ethical and cultural issues as they are derived from animal sources.…”
Section: Polymers and Cross-linking Agentsmentioning
confidence: 99%
“…The uniqueness of hydrogels in terms of their physical properties makes them ideal candidates for embedding, carrying and releasing drugs and other biologically active substances [ 13 ]. The ability to absorb large amounts of water and their flexibility are properties that make hydrogels closely resemble biological tissues [ 14 ]. Moreover, another advantage is given by the versatility of preparation methods, as the hydrogels can be obtained either by physical cross-linking (based on the intermolecular hydrophobic interactions, electrostatic attraction or hydrogen bonding), or by permanent chemical cross-linking of the polymer chains through covalent bonding between functional groups [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%